2021
DOI: 10.1002/adhm.202002197
|View full text |Cite
|
Sign up to set email alerts
|

An NRP1/MDM2‐Targeted D‐Peptide Supramolecular Nanomedicine for High‐Efficacy and Low‐Toxic Liver Cancer Therapy

Abstract: Supramolecular nanomedicines based on self‐assembly of D‐peptides have been of great interest as potential candidates for cancer therapy. Neuropilin‐1 (NRP1) and mouse double minute 2 (MDM2) have been considered as the anticancer targets because of their overexpression in cancers. However, NRP1/MDM2‐targeted D‐peptide supramolecular nanomedicines remain unreported. Here, a potent anticancer D‐peptide supramolecular nanomedicine targeting NRP1 and MDM2, termed as NMTP‐5, is identified by using structure‐based v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The structure-based pharmacophore model has become an important tool in drug discovery ( Yang et al, 2020 ; Zhou et al, 2021 ). Previous studies have shown that MOE can be applied to obtain the pharmacophore features on the ligand binding to the target protein by analyzing the protein-ligand interaction of its crystal structure ( Zhou et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure-based pharmacophore model has become an important tool in drug discovery ( Yang et al, 2020 ; Zhou et al, 2021 ). Previous studies have shown that MOE can be applied to obtain the pharmacophore features on the ligand binding to the target protein by analyzing the protein-ligand interaction of its crystal structure ( Zhou et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Structure-based virtual screening that combines structure-based pharmacophore modeling and molecular docking is one of the methods used in CADD and it enables screening of many compounds in a relatively short time compared to the high throughput screening via laboratory experiments ( McInnes, 2007 ; Yang et al, 2020 ). The previous studies have successfully identified kinds of novel and effective inhibitors by using such a virtual screening strategy ( Yang et al, 2020 ; Zhou et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To satisfy the design criteria illustrated in Figure 1, we designed the supramolecular gelator precursor cyclic-1a, the C 10 H 7 CH 2 C(O)CFFYKCGGRRGKGGHHHRRGDS sequence (disulfide bond cyclization). The cyclic-1a contains the following four distinct segments: 1) the naphthyl group (C 10 H 7 CH 2 -) for providing the hydrophobic force to improve the ability of self-assembly in aqueous environment (Zhou et al, 2021); 2) the tetrapeptide (FFYK) segment (being made of D-amino acids) being the major building block to act as both a donor and an acceptor of hydrogen bonds (Zhou et al, 2021); 3) the disulfided cysteine (Cys) motif as a trigger of GSH reduction, which was responsible for the first order nanofiber self-assembly; and 4) the peptide sequence (GGRRGKGGHHHRRGDS), whose cleavage by CB confers on the molecule the ability of the second order self-assembly.…”
Section: Synthesis and Characterization Of The Supramolecular Gelator...mentioning
confidence: 99%
“…Linear peptides have been designed to undergo self-assembly in response to enzymatic catalysis in biological microenvironments (Rudra et al, 2010;Rudra et al, 2012). As a useful strategy for generating supramolecular nanofibers/hydrogels, linear peptide-based hydrogelations show promising applications in cell fate control, drug delivery, immune modulation, biosensing, and regenerative medicine (Habibi et al, 2016;Acar et al, 2017;Zhou et al, 2021). Despite many advantages of linear peptides as the precursors for enzyme-triggered hydrogelation, linear peptides are easily degraded by extracellular serum proteases before entering the cytoplasm of cells (Lian et al, 2014;Yang et al, 2020), which greatly restricts their clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative way to identify L- and D-peptide ligands, which does not suffer from the abovementioned restrictions, is computational modelling of PPIs [ 22 ]. Recent publications have shown the feasibility of identifying biologically active D-peptide ligands by modelling the structure of short helical D-peptide segments with molecular dynamics (MD) simulations and by screening peptide libraries generated this way for ligand-target interactions via molecular docking [ 23 , 24 ]. These programs enable the high-throughput in silico screening of peptide libraries; however, with increasing peptide length, the size of peptide libraries and, consequently, the search space and computational cost for docking-based screenings increase exponentially to a point where they are simply too large to be systematically explored.…”
Section: Introductionmentioning
confidence: 99%